Reversing the spiral : the population, agriculture, and environment nexus in Sub-Saharan Africa - Cleaver, Kevin M.; Schreiber, Götz A. (Washington, D.C. : World Bank, 1994)
This book recommends concrete and implementable strategies to intensify agriculture, increase demand for smaller families, reform land tenure practices, conserve the environment, and address the special problems of women. Also for empowered farmers to manage their own development.
Includes bibliographical references (p. 261-293).
occ 17/01/2019
Loans
Keywords: Human ecology; Agriculture and state; Agriculture - environmental aspect; Economic conditions; Environmental conditions; Africa, Sub-Saharan